Remembering a legend : Chinua Achebe - Emenyo̲nu, Ernest, 1939-; Nnolim, Charles E. (African Heritage Press, 2014)
Remembering a Legend: Chinua Achebe recaptures for the literary world the inimitable legacies of Chinua Achebe (1930-2013), Africa's leading novelist and literary philosopher of the 20th century. It addresses the questions of Achebe's role in establishing the African art of the novel, his theories and standards for the criticism of African writing. The volume articulates unequivocally how Achebe provided the message and pioneered a confident voice to African writers to express the message with audacity; repudiate without equivocation, any form of distortions of African past and present realiti.